The Stabilization and Association Agreement between Bosnia and Herzegovina and the European Union : Impacts of the Adaptation Protocol on the Agriculture and Food Sector - World Bank Group (World Bank, Washington, DC, 2017)
The objective of this note is to provide insights into the potential effect of the adaptation protocol (AP) on imports of European Union (EU) agricultural, food and fisheries products into Bosnia and Herzegovina (BiH). We adapt and calibrate the Tariff Reform Impact Simulation Tool (TRIST), a partial equilibrium trade model developed by the World Bank, to estimate the impact of imports from the EU on consumption and local production of agricultural and food products for which disaggregated data is available. The impact of a change in tariffs is modeled in a simple partial equilibrium trade model with imperfect substitution between imports from different trading partners and domestic production. The team benefitted from the cooperation with the counterparts (MOFTER and Ministries) regarding data and inputs. This analysis has important limitations and the results should be considered as indicative estimates. This is a trade analysis that only partially reflects the overall impact and provides a very short term perspective on trade interactions. TRIST is a static model that depends on the availability of disaggregated agricultural data on both imports and production.